ZIPF’S LAW AND WRITINGS ON LIS - Sen, B K; Khong, Wye Keen; Lee, Soo Hoon; Lim, Bee Ling; Abdullah, Mohd Rafae; Ting, Chang Nguan; Wee, Siu Hiang (Malaysian Journal of Library and Information Science, 1998)
Presents the results of a study conducted to find out the validity of Zipf’s law related to the word length and the frequency of its uses in the case of library and information science literature. The results obtained from the analysis of six different samples obey Zipf’s law in all the cases with small deviations. The result provided by the sample comprising about 5,800 words fits the law best with just one deviation. The main exception is found to be one-letter words.